Conference on Lasers and Electro-Optics 2010 2010
DOI: 10.1364/qels.2010.qthi2
|View full text |Cite
|
Sign up to set email alerts
|

High-Rate Quantum Key Distribution with Superconducting Nanowire Single Photon Detectors

Abstract: We demonstrate the potential for 1.85 Mbit/s secure key rates over 101 km of fiber, >100 times faster than previously demonstrated, using the differential phase shift quantum key distribution protocol and superconducting nanowire single-photon detectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Intrinsic device detection efficiencies (η dde ) of 57% for 1550 nm photons (and 67% at 1064 nm), at 1.8_K, have been demonstrated by embedding a 3 µm x 3_µm nanowire meander SNSPD inside an optical cavity in order to increase η absorption (Figure 2(c)) [28]. This design has been refined further (via a buried oxide and a four pixel layout) to achieve 87% η dde at 1550 nm [39]. Efficient optical coupling is required to convert these intrinsic values into practical system efficiencies, as discussed in section 2.4.2.…”
Section: Enhancing Absorption Efficiencymentioning
confidence: 99%
“…Intrinsic device detection efficiencies (η dde ) of 57% for 1550 nm photons (and 67% at 1064 nm), at 1.8_K, have been demonstrated by embedding a 3 µm x 3_µm nanowire meander SNSPD inside an optical cavity in order to increase η absorption (Figure 2(c)) [28]. This design has been refined further (via a buried oxide and a four pixel layout) to achieve 87% η dde at 1550 nm [39]. Efficient optical coupling is required to convert these intrinsic values into practical system efficiencies, as discussed in section 2.4.2.…”
Section: Enhancing Absorption Efficiencymentioning
confidence: 99%
“…The simulation results are show in Fig.3: the QBER is about 5% for a time jitter of 70ps. The time jitter of a state-of-the-art superconducting nanowire SPD (SNSPD) can be as small as 40ps [6], and the resulting intrinsic QBER is about 0.05%. QBER is about 5% for a time jitter of 70ps.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In addition, they are capable of turnkey, continuous, and stable operation without any liquid cryogen or the need for a wavelength conversion and gating system, making them more attractive. Practical multi channel SNSPD systems have been employed in many QKD experiments and quantum optics studies, and demonstrated their superiority [3]- [9].…”
Section: Introductionmentioning
confidence: 99%